Inequalities for the Psi and k-Gamma functions - Nantomah, Kwara (Global Journal of Mathematical Analysis, 2014)
In this paper, the authors establish some inequalities involving the Psi and k-Gamma functions. The procedure utilizes some monotonicity properties of some functions associated with the Psi and k-Gamma functions. Keywords: Gamma function, k-Gamma function, Psi function, Inequality. MSC: 33B15, 26A48.